1989
DOI: 10.1017/s000335610000430x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma β-endorphin and cortisol concentrations in lambs after handling, transport and slaughter

Abstract: The effects of the routine stressful stimuli of handling, transport and slaughter on the plasma concentrations of cortisol and (3-endorphin have been studied in lambs. Blood samples were obtained from group 1 lambs after rounding up, after transport and at slaughter. Group 2 lambs were treated similarly except that blood was collected only at slaughter. Group 3 lambs served as controls and were blood sampled twice daily for 5 days to accustom them to handling before being slaughtered. Plasma cortisol and P-end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Blood analyses Plasma cortisol concentrations have been used as a reliable indicator of stress in lamb (Fordham et al, 1989). Furthermore, LDH activity is associated with stress and muscle fatigue (weariness) (Broom, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Blood analyses Plasma cortisol concentrations have been used as a reliable indicator of stress in lamb (Fordham et al, 1989). Furthermore, LDH activity is associated with stress and muscle fatigue (weariness) (Broom, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the β-EP response to a severe stress can be attenuated by prior exposure to a milder form of stress [29]. Therefore, cows not showing elevation of ir-β-EP level at parturition, which had high plasma ir-β-EP levels prior to parturition, may have had a certain stress before calving, and the sensitivity to pain in these cows might have reduced by the time of labor.…”
Section: Discussionmentioning
confidence: 99%
“…Driving the flock by the shepherd provoked behavioural reactions, such as trotting and vocalisation and increases in heart rate and cortisol (Fordham et al, 1989;Baldock and Sibly, 1990). Sheep little used to handling show stronger reactions (Bassett and Hinks, 1969).…”
Section: Sheepmentioning
confidence: 99%